Penerapan Komunikasi Pemasaran terhadap Keputusan Pembelian Konsumen - Rima Rizki Syahputri; Nuri Aslami (LPPM IAI Nasional Laa Roiba Bogor, 2021)
In the field of marketing, globalization has had a significant impact. Where the market potential is growing, but there is a drawback, namely the increasingly fierce and difficult competition. As a result, marketing in this era of globalization requires more than just producing product improvements, setting lower rates, and distributing goods continuously. Companies, on the other hand, need good marketing communications to promote their products, strengthen their brand image, and generate purchasing decisions. The purpose of this study is to see how the communication mix affects customer purchasing decisions. Advertising, personal selling, sales promotion, direct marketing, and public relations are the five main aspects that make up the marketing communications mix. Where these five parts come together to fulfill the purpose of marketing communication, namely improving product image, which leads to product purchase. Keywords: Marketing, Marketing Communication, Purchasing